An Observational Study of Perioperative Risk Associated with Aortic Stenosis in Non-Cardiac Surgery. Issue 2 (March 2018) - MacIntyre, P. A.; Scott, M.; Seigne, R.; Clark, A.; Deveer, F.; Minchin, I.
This prospective multicentre observational study investigated the risk of non-cardiac surgery in patients with moderate or severe aortic stenosis (AS). Patients with AS undergoing non-cardiac surgery in five New Zealand hospitals between August 2011 and September 2015 were studied. Preoperative variables were analysed for a significant association with postoperative major adverse cardiac events (MACE) and 30–day mortality. Of the 147 patients recruited, 13 (9%) died within 30 days and 33 (22%) had a MACE. Using univariate analysis, patients with severe AS had four times higher 30-day mortality than patients with moderate AS (16% versus 4%, P=0.007). Other factors associated with increased 30-day mortality included having a smaller aortic valve area, smaller dimensionless severity index, concomitant mitral regurgitation, and higher overall surgical risk. Patients with symptoms attributable to AS had a higher incidence of MACE compared to patients without symptoms (36% versus 16%, P=0.011). Variables significantly associated with both 30-day mortality and MACE were age, American Society of Anesthesiologists physical status, emergency surgery, New York Heart Association classification, preoperative albumin level, frailty, and history of congestive heart failure. Using multivariate analysis, emergency surgery, symptoms attributable to AS, preoperative albumin level, and AVA remained significantly associated with adverse outcome. While these findings should be interpreted with caution due to the observational nature of the study, limited power and multiple simultaneous comparisons, they suggest that patients with severe AS have a higher risk of adverse outcome after non-cardiac surgery than patients with moderate AS.